Glenoid bone grafting in primary anatomic total shoulder arthroplasty: a systematic review. (October 2021) - Zhang, Betty; Niroopan, Gavinn; Gohal, Chetan; Alolabi, Bashar; Leroux, Timothy; Khan, Moin
Background: Primary anatomic total shoulder arthroplasty can be challenging in patients with complex glenoid wear patterns and bone loss. Severe retroversion (>15°) or significant bone loss may require bone grafting. This review summarizes the rate of revision and long-term outcomes of anatomic total shoulder arthroplasty with bone graft. Methods: A systematic search of MEDLINE, Embase, PubMed, and CENTRAL databases was conducted from the date of inception to 23 October 2018. Two reviewers independently screened articles for eligibility and extracted data for analysis. The primary outcome was rate of revision. The secondary outcomes were rate of component loosening, functional outcome, and range of motion. Results: Of the 1056 articles identified in the search, 26 underwent full-text screening and 7 articles were included in the analysis. All procedures were one-stage anatomic total shoulder arthroplasties. The rate of revision was 5.4% with component loosening and infection listed as indications over a weighted mean follow-up period of 6.3 years. Complications occurred in 12.6% of patients. Conclusion: Glenoid bone grafting in anatomic total shoulder arthroplasty results in comparable revision rates and improvement in pain compared to augmented glenoid components and reverse shoulder arthroplasty. Due to the low quality of evidence, further prospective studies should be conducted. Level of evidence: IV